Adhesive for fiber-reinforced polyimide composite material / metal bonding and preparation method thereof

Combination of N,N'-(4,4'-methylenediphenyl)bismaleimide and crosslinking agent dispersion in fiber reinforced polyimide composite material and metal bonding adhesive , solves the problem of insufficient shear strength and high temperature resistance of existing adhesives, and realizes high shear strength and good uniformity adhesive preparation, suitable for bonding applications in high temperature environments.

CN118813142BActive Publication Date: 2024-12-27FUYOUTE (SHANDONG) NEW MATERIAL TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411297502.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The bonding adhesives between existing fiber-reinforced polyimide composite materials and metals have shortcomings in terms of shear strength and high temperature resistance, and have poor uniformity, resulting in poor bonding effect at high temperatures.

Method used

Mixing N,N'-(4,4'-methylene diphenyl)bismaleimide, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride in a nitrogen atmosphere and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and a crosslinking agent dispersion was added. Through Michael addition and crosslinking reaction, a high shear strength and high temperature resistance were prepared. adhesive.

Benefits of technology

It improves the shear strength and high temperature resistance of the adhesive, ensures that good bonding performance remains at high temperatures, and avoids phase separation, significantly improving the bond uniformity between fiber-reinforced polyimide composite materials and metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an adhesive for fiber-reinforced polyimide composite material / metal bonding and a preparation method thereof, belonging to the field of polymer adhesive preparation. The preparation method comprises the following steps of mixing N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide in a nitrogen atmosphere, stirring the mixture at room temperature for 5-10 minutes, adding 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion, and continuing stirring for 5-6 hours to obtain the adhesive for fiber-reinforced polyimide composite material / metal bonding. The adhesive prepared by the invention has high shear strength, high temperature resistance and good uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer adhesive preparation, and in particular to an adhesive for fiber-reinforced polyimide composite material / metal bonding and a preparation method thereof. Background Art

[0002] Polyimide is a kind of aromatic heterocyclic high-performance polymer material with imide ring structure as the characteristic unit. It has excellent thermal stability and high temperature resistance, as well as excellent mechanical properties, electrical properties, optical properties, radiation resistance and solvent resistance, and is widely used in many technical fields. At present, the application of fiber-reinforced polyimide composites / metal hybrid structures in lightweight engineering parts such as aerospace, transportation manufacturing and medical equipment has attracted widespread attention. The partial replacement of metal with fiber-reinforced polyimide composites / metal hybrid structures is a feasible solution to achieve structural lightweighting, which can reduce the weight of the structure by 25-30%, and has huge energy-saving potential and economic benefits for industry development. Bonding fiber-reinforced polyimide composites to metals with adhesives is a very effective connection method, which has the characteristics of simple process, convenient operation, high efficiency and speed.

[0003] The bonding between fiber-reinforced polyimide composites and metals belongs to the bonding between polymers and metals, and its bonding mechanisms include mechanical locking, surface wetting and adsorption, electrostatic action, and chemical bonding. Among them, mechanical locking is to penetrate the adhesive into the surface defects of the material, and after hardening, an anchoring effect and a locking effect are established at the interface, which increases the contact area and thus improves the bonding strength; surface wetting and adsorption are the interactions between atoms and molecules on the surface of the material formed by secondary forces, resulting in bonding effects at the interface between different materials; electrostatic action is the electron transfer between the interfaces of the two materials, resulting in electrical differences between the interfaces, generating electrostatic attraction and improving bonding strength; chemical bonding is the formation of covalent bonds or ionic bonds between the adhesive and the substrate, generating the highest bonding strength.

[0004] Considering that fiber-reinforced polyimide composite material / metal hybrid structures are often used as load-bearing parts, when using a chemical bonding bonding mechanism, that is, bonding the two with an adhesive to form a hybrid structure, it is necessary to have higher shear strength and high temperature resistance.

[0005] Regarding the bonding of polyimide and metal materials, Chinese patent CN103612464B discloses a double-sided flexible copper clad laminate and a preparation method thereof, which uses bisphenol A epoxy adhesive to bond polyimide and copper material, but has low shear strength and poor high temperature resistance; Chinese patent CN103502328B discloses an adhesive for bonding polyimide resin, which uses polycarbonate containing siloxane components to bond polyimide resin, although it has high shear strength, it has poor high temperature resistance; Japanese patent JP62-278687 discloses introducing siloxane segments into the polyimide skeleton structure, which is beneficial for bonding copper foil and polyimide film, but the glass transition temperature of the polyimide adhesive system is low, resulting in poor high temperature resistance, and phase separation is also prone to occur, resulting in poor uniformity of the prepared polyimide adhesive. Summary of the invention

[0006] The present invention aims to provide an adhesive for bonding fiber-reinforced polyimide composite materials to metals and a preparation method thereof. The prepared adhesive has high shear strength, high temperature resistance and good uniformity.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing an adhesive for bonding fiber-reinforced polyimide composite materials to metals, comprising: mixing N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide in a nitrogen atmosphere, stirring at a stirring speed of 300-400 rpm for 5-10 min at room temperature, adding 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion, and continuing stirring for 5-6 h to obtain an adhesive for bonding fiber-reinforced polyimide composite materials to metals;

[0009] In the preparation of the adhesive, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 14-16%;

[0010] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7-8:92-93:100;

[0011] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:10-12;

[0012] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14-15:1;

[0013] The preparation method of the crosslinking agent dispersion comprises the following steps: hydroxy silicone oil coating, zinc hydroxide coating, surface modification, and dispersion;

[0014] The hydroxy silicone oil coating comprises mixing white carbon black and dimethyl hydroxy silicone oil and then ball milling to obtain hydroxy silicone oil coated white carbon black;

[0015] In the hydroxy silicone oil coating, the mass ratio of white carbon black to dimethyl hydroxy silicone oil is 270-275:27-30;

[0016] The particle size of the white carbon black is 100 nm;

[0017] The viscosity of the dimethyl hydroxy silicone oil at 25° C. is 100 mPa·s;

[0018] The ball-to-material ratio during ball milling is 5-6:1, the rotation speed is 300-350rpm, and the time is 35-45min;

[0019] The zinc hydroxide coating comprises mixing zinc chloride, sodium dodecylbenzene sulfonate and deionized water, stirring at a stirring speed of 300-500 rpm for 30-40 minutes at room temperature, adding hydroxy silicone oil to coat the white carbon black, continuing to stir for 40-50 minutes, centrifuging at a centrifugal speed of 11000-12000 rpm for 9-10 minutes, taking a precipitate, mixing the precipitate with a sodium hydroxide aqueous solution, stirring at a stirring speed of 300-500 rpm for 40-50 minutes at room temperature, centrifuging at a centrifugal speed of 11000-12000 rpm for 9-10 minutes, taking a precipitate, washing it with deionized water for 3-4 times, and drying it at 70-80° C. to obtain zinc hydroxide coated white carbon black;

[0020] In the zinc hydroxide coating, the mass ratio of zinc chloride, sodium dodecylbenzene sulfonate, deionized water, hydroxy silicone oil coated white carbon black, and sodium hydroxide aqueous solution is 200-250:25-26:7000-8000:570-600:3800-4000;

[0021] The mass concentration of the sodium hydroxide aqueous solution is 5%;

[0022] The surface modification comprises mixing N,N-dimethyl-3-aminopropyltrimethoxysilane and anhydrous ethanol, stirring at 40-45° C. at a stirring speed of 100-150 rpm for 30-40 min, adding zinc hydroxide to coat white carbon black, continuing stirring for 10-11 h, centrifuging at a centrifugal speed of 11000-12000 rpm for 9-10 min, taking a precipitate, washing it with anhydrous ethanol for 3-4 times, and drying it at 70-80° C. to obtain a crosslinking agent;

[0023] In the surface modification, the mass ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane, anhydrous ethanol, and zinc hydroxide-coated white carbon black is 18-20:7500-8000:550-600;

[0024] The dispersion comprises mixing a crosslinking agent and N,N-dimethylacetamide, and then ultrasonically shaking at 20-25 kHz for 10-15 minutes at room temperature to obtain a crosslinking agent dispersion;

[0025] In the dispersion, the mass ratio of the crosslinking promoter to N,N-dimethylacetamide is 5:100-110.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The preparation method of the adhesive for fiber-reinforced polyimide composite material / metal bonding of the present invention comprises adding N,N'-(4,4'-methylenediphenyl)bismaleimide and a crosslinking agent dispersion during the preparation; wherein N,N'-(4,4'-methylenediphenyl)bismaleimide can undergo Michael addition with 1,3-bis(3-aminopropyl)tetramethyldisiloxane, specifically, the carbon-carbon double bond in N,N'-(4,4'-methylenediphenyl)bismaleimide can undergo Michael addition with the amino group in 1,3-bis(3-aminopropyl)tetramethyldisiloxane, and N,N'-(4,4'-methylenediphenyl)bismaleimide can undergo Michael addition with the amino group in 1,3-bis(3-aminopropyl)tetramethyldisiloxane. The structure of diphenyl) bismaleimide is similar to that of polyimide, so it has a strong affinity with polyimide, thereby improving the shear strength and high temperature resistance of the adhesive; the preparation method of the crosslinking agent dispersant includes hydroxy silicone oil coating, zinc hydroxide coating, surface modification, and dispersion, wherein the hydroxy silicone oil coating is to mix the hydroxy silicone oil with white carbon black and then perform ball milling, during which the hydroxy silicone oil is fixed to the surface of the white carbon black by intermolecular forces to obtain hydroxy silicone oil-coated white carbon black; the zinc hydroxide coating is to mix zinc chloride, a surfactant, deionized water, and hydroxy silicone oil-coated white carbon black, the surfactant emulsifies the hydroxy silicone oil-coated white carbon black and then disperses it in water, and the hydrophilicity of the surfactant The end is outward, the hydrophobic end is inward, and the hydrophilic end is combined with zinc chloride. After centrifugation, zinc ion-coated white carbon black is obtained, and then the zinc ion-coated white carbon black is added to an aqueous sodium hydroxide solution, and the zinc ion is combined with hydroxide to obtain zinc hydroxide-coated white carbon black; the surface is modified by using an ethanol solution of N,N-dimethyl-3-aminopropyltrimethoxysilane to graft the zinc hydroxide-coated white carbon black to obtain a cross-linking promoter with N,N-dimethyl-3-aminopropyltrimethoxysilane grafted on the surface; finally, the cross-linking promoter is dispersed in N,N-dimethylacetamide to obtain a cross-linking promoter dispersion; therefore, the structure of the cross-linking promoter is white carbon black as the core, and from the inside to the outside, it is hydroxy silicone oil layer, a surfactant layer, a zinc hydroxide layer, and an N,N-dimethyl-3-aminopropyltrimethoxysilane layer, wherein the N,N-dimethyl-3-aminopropyltrimethoxysilane layer can promote the Michael addition of amino groups and carbon-carbon double bonds; the N,N-dimethyl-3-aminopropyltrimethoxysilane layer can also promote the uniform dispersion of cross-linking particles, further improve the dispersibility of other components in the adhesive, avoid phase separation, and thus improve the uniformity of the adhesive; when the adhesive is cured at high temperature, the zinc hydroxide undergoes thermal decomposition, and the hydroxy silicone oil layer can promote the cross-linking between the adhesives and act as a cross-linking point, thereby improving the shear strength and high temperature resistance of the adhesive;

[0028] (2) The preparation method of the adhesive for fiber-reinforced polyimide composite material / metal bonding of the present invention has a large shear strength. When bonding a glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite material plate to an aluminum metal plate, the shear strength at 25°C can reach 27.8-29.1MPa; when bonding a glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite material plate to a magnesium metal plate, the shear strength at 25°C can reach 29.2-29.8MPa; when bonding a carbon fiber reinforced polyimide (glass fiber content 20wt%) composite material plate to a magnesium metal plate, the shear strength at 25°C can reach 29.2-29.8MPa; When bonding maleimide (carbon fiber content 30wt%) composite plates to titanium metal plates, the shear strength at 25°C can reach 30.1-31.4MPa; when bonding glass fiber reinforced bismaleimide (glass fiber content 20wt%) composite plates to aluminum metal plates, the shear strength at 25°C can reach 30.2-31.3MPa; when bonding carbon fiber reinforced bismaleimide (carbon fiber content 30wt%) composite plates to magnesium metal plates, the shear strength at 25°C can reach 28.8-31.2MPa;

[0029] (3) The preparation method of the adhesive for fiber-reinforced polyimide composite material / metal bonding of the present invention has good high temperature resistance. When bonding a glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite material plate and an aluminum metal plate, the obtained test sample is heated to 400°C at a heating rate of 10°C / min, kept warm for 30 minutes, and naturally cooled to room temperature. The shear strength at 25°C can reach 27.5-28.6MPa;

[0030] (4) The method for preparing the adhesive for fiber-reinforced polyimide composite material / metal bonding of the present invention has good uniformity. After the adhesive obtained by the present invention is sealed and left to stand for 30 days, there is no phase separation phenomenon. DETAILED DESCRIPTION

[0031] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0032] Example 1

[0033] A method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding, specifically comprising:

[0034] In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at 300 rpm for 5 min at room temperature, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion were added, and stirring was continued for 5 h to obtain an adhesive for fiber reinforced polyimide composite material / metal bonding;

[0035] Among them, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 14%;

[0036] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7:93:100;

[0037] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:10;

[0038] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14:1;

[0039] The preparation method of the crosslinking agent dispersion is as follows:

[0040] 1. Hydroxy silicone oil coating: 270g of white carbon black and 27g of dimethyl hydroxy silicone oil were mixed and ball milled, and the ball-to-material ratio during ball milling was controlled to be 5:1, the rotation speed was 300rpm, and the time was 35min to obtain hydroxy silicone oil-coated white carbon black;

[0041] The particle size of the white carbon black is 100 nm;

[0042] The viscosity of the dimethyl hydroxy silicone oil at 25° C. is 100 mPa·s;

[0043] 2. Zinc hydroxide coating: 200g zinc chloride, 25g sodium dodecylbenzene sulfonate, and 7000g deionized water were mixed, stirred at a stirring speed of 300rpm for 30min at room temperature, 570g hydroxy silicone oil was added to coat the white carbon black, and the stirring was continued for 40min. The mixture was centrifuged at a centrifugal speed of 11000rpm for 9min, and the precipitate was taken. The precipitate was mixed with 3800g of a sodium hydroxide aqueous solution with a mass concentration of 5%, and the mixture was stirred at a stirring speed of 300rpm for 40min at room temperature, and the mixture was centrifuged at a centrifugal speed of 11000rpm for 9min. The precipitate was taken, washed with deionized water for 3 times, and dried at 70°C to obtain zinc hydroxide-coated white carbon black;

[0044] 3. Surface modification: 18 g of N, N-dimethyl-3-aminopropyltrimethoxysilane and 7500 g of anhydrous ethanol were mixed, stirred at 40°C at a stirring speed of 100 rpm for 30 min, 550 g of zinc hydroxide-coated white carbon black was added, stirring was continued for 10 h, centrifuged at a centrifugal speed of 11000 rpm for 9 min, the precipitate was taken, washed with anhydrous ethanol for 3 times, and dried at 70°C to obtain a cross-linking agent;

[0045] 4. Dispersion: Mix 5 g of a crosslinking agent and 100 g of N,N-dimethylacetamide, and ultrasonically vibrate at 20 kHz for 10 min at room temperature to obtain a crosslinking agent dispersion.

[0046] This embodiment also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0047] Example 2

[0048] A method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding, specifically comprising:

[0049] In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at room temperature at a stirring speed of 350 rpm for 6 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion were added, and stirring was continued for 5.5 hours to obtain an adhesive for fiber reinforced polyimide composite material / metal bonding;

[0050] Among them, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 15%;

[0051] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7.5:92.5:100;

[0052] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:11;

[0053] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14.4:1;

[0054] The preparation method of the crosslinking agent dispersion is as follows:

[0055] 1. Hydroxy silicone oil coating: 272g of white carbon black and 28g of dimethyl hydroxy silicone oil were mixed and ball milled, and the ball-to-material ratio during ball milling was controlled to be 5:1, the rotation speed was 350rpm, and the time was 40min to obtain hydroxy silicone oil-coated white carbon black;

[0056] The particle size of the white carbon black is 100 nm;

[0057] The viscosity of the dimethyl hydroxy silicone oil at 25° C. is 100 mPa·s;

[0058] 2. Zinc hydroxide coating: 220g zinc chloride, 25.5g sodium dodecylbenzene sulfonate, and 7500g deionized water were mixed, stirred at room temperature at a stirring speed of 400rpm for 35min, 580g hydroxy silicone oil was added to coat the white carbon black, and the stirring was continued for 45min. The mixture was centrifuged at a centrifugal speed of 11000rpm for 9min, and the precipitate was taken. The precipitate was mixed with 3900g of a sodium hydroxide aqueous solution with a mass concentration of 5%, and stirred at room temperature at a stirring speed of 400rpm for 45min. The mixture was centrifuged at a centrifugal speed of 11000rpm for 9min, and the precipitate was taken. The mixture was washed with deionized water for 3 times, and dried at 75°C to obtain zinc hydroxide-coated white carbon black;

[0059] 3. Surface modification: 19 g of N, N-dimethyl-3-aminopropyltrimethoxysilane and 7800 g of anhydrous ethanol were mixed, stirred at 40 ° C at a stirring speed of 120 rpm for 35 min, 570 g of zinc hydroxide-coated white carbon black was added, and the stirring was continued for 10.5 h. The mixture was centrifuged at a centrifugal speed of 11000 rpm for 9 min, and the precipitate was taken, washed with anhydrous ethanol for 3 times, and dried at 75 ° C to obtain a cross-linking agent;

[0060] 4. Dispersion: Mix 5 g of cross-linking agent and 105 g of N,N-dimethylacetamide, and ultrasonically vibrate at 20 kHz for 12 min at room temperature to obtain a cross-linking agent dispersion.

[0061] This embodiment also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0062] Example 3

[0063] A method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding, specifically comprising:

[0064] In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at room temperature at a stirring speed of 350 rpm for 8 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion were added, and stirring was continued for 5.5 hours to obtain an adhesive for fiber-reinforced polyimide composite material / metal bonding;

[0065] Among them, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 15.5%;

[0066] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7.8:92.2:100;

[0067] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:11.5;

[0068] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14.8:1;

[0069] The preparation method of the crosslinking agent dispersion is as follows:

[0070] 1. Hydroxy silicone oil coating: 275g of white carbon black and 29g of dimethyl hydroxy silicone oil were mixed and ball milled, and the ball-to-material ratio during ball milling was controlled to be 6:1, the rotation speed was 350rpm, and the time was 40min to obtain hydroxy silicone oil-coated white carbon black;

[0071] The particle size of the white carbon black is 100 nm;

[0072] The viscosity of the dimethyl hydroxy silicone oil at 25° C. is 100 mPa·s;

[0073] 2. Zinc hydroxide coating: 240g zinc chloride, 25.5g sodium dodecylbenzene sulfonate and 7800g deionized water were mixed, stirred at room temperature at a stirring speed of 400rpm for 40min, 590g hydroxy silicone oil was added to coat the white carbon black, and the stirring was continued for 45min. The mixture was centrifuged at a centrifugal speed of 12000rpm for 10min, and the precipitate was taken. The precipitate was mixed with 3900g of a 5% sodium hydroxide aqueous solution by mass concentration, stirred at room temperature at a stirring speed of 400rpm for 45min, and centrifuged at a centrifugal speed of 12000rpm for 10min. The precipitate was taken, washed with deionized water for 4 times, and dried at 80°C to obtain zinc hydroxide coated white carbon black;

[0074] 3. Surface modification: 19 g of N, N-dimethyl-3-aminopropyltrimethoxysilane and 7900 g of anhydrous ethanol were mixed, stirred at 45 ° C at a stirring speed of 150 rpm for 35 min, 590 g of zinc hydroxide-coated white carbon black was added, and the stirring was continued for 11 h. The mixture was centrifuged at a centrifugal speed of 12000 rpm for 10 min, the precipitate was taken, washed with anhydrous ethanol for 4 times, and dried at 80 ° C to obtain a cross-linking agent;

[0075] 4. Dispersion: Mix 5 g of crosslinking agent and 110 g of N,N-dimethylacetamide, and ultrasonically vibrate at 25 kHz for 10 min at room temperature to obtain a crosslinking agent dispersion.

[0076] This embodiment also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0077] Example 4

[0078] A method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding, specifically comprising:

[0079] In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at room temperature at a stirring speed of 400 rpm for 10 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion were added, and stirring was continued for 6 hours to obtain an adhesive for fiber-reinforced polyimide composite material / metal bonding;

[0080] Among them, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 16%;

[0081] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 8:92:100;

[0082] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:12;

[0083] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 15:1;

[0084] The preparation method of the crosslinking agent dispersion is as follows:

[0085] 1. Hydroxy silicone oil coating: 275g of white carbon black and 30g of dimethyl hydroxy silicone oil were mixed and ball milled, and the ball-to-material ratio during ball milling was controlled to be 6:1, the rotation speed was 350rpm, and the time was 45min to obtain hydroxy silicone oil-coated white carbon black;

[0086] The particle size of the white carbon black is 100 nm;

[0087] The viscosity of the dimethyl hydroxy silicone oil at 25° C. is 100 mPa·s;

[0088] 2. Zinc hydroxide coating: 250g zinc chloride, 26g sodium dodecylbenzene sulfonate, and 8000g deionized water were mixed, stirred at room temperature at a stirring speed of 500rpm for 40min, 600g hydroxy silicone oil was added to coat the white carbon black, and the stirring was continued for 50min. The mixture was centrifuged at a centrifugal speed of 12000rpm for 10min, and the precipitate was taken. The precipitate was mixed with 4000g of a 5% sodium hydroxide aqueous solution by mass concentration, and stirred at room temperature at a stirring speed of 500rpm for 50min, and the mixture was centrifuged at a centrifugal speed of 12000rpm for 10min. The precipitate was taken, washed with deionized water for 4 times, and dried at 80°C to obtain zinc hydroxide coated white carbon black;

[0089] 3. Surface modification: 20 g of N, N-dimethyl-3-aminopropyltrimethoxysilane and 8000 g of anhydrous ethanol were mixed, stirred at 45 ° C at a stirring speed of 150 rpm for 40 min, 600 g of zinc hydroxide-coated white carbon black was added, and the stirring was continued for 11 h. The mixture was centrifuged at a centrifugal speed of 12000 rpm for 10 min, the precipitate was taken, washed with anhydrous ethanol for 4 times, and dried at 80 ° C to obtain a cross-linking agent;

[0090] 4. Dispersion: Mix 5 g of the crosslinking agent with 110 g of N,N-dimethylacetamide, and ultrasonically vibrate at 25 kHz for 15 min at room temperature to obtain a crosslinking agent dispersion.

[0091] This embodiment also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0092] Comparative Example 1

[0093] Based on the preparation method of the adhesive for fiber-reinforced polyimide composite material / metal bonding in Example 1, the addition of N,N'-(4,4'-methylenediphenyl)bismaleimide is omitted, and the preparation method is specifically changed to:

[0094] In a nitrogen atmosphere, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at room temperature at a stirring speed of 300 rpm for 5 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride, and a crosslinking agent dispersion were added, and stirring was continued for 5 hours to obtain an adhesive for fiber-reinforced polyimide composite material / metal bonding;

[0095] Among them, the sum of the mass concentrations of 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 14%;

[0096] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 93:100;

[0097] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:10;

[0098] The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14:1;

[0099] The crosslinking promoter dispersion is the same as that in Example 1.

[0100] This comparative example also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0101] Comparative Example 2

[0102] Based on the preparation method of the adhesive for fiber-reinforced polyimide composite material / metal bonding in Example 1, the addition of the crosslinking promoter dispersion is omitted, and the preparation method is specifically changed to:

[0103] In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide were mixed, stirred at room temperature at a stirring speed of 300 rpm for 5 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 4-phenylethynylphthalic anhydride were added, and stirring was continued for 5 hours to obtain an adhesive for fiber reinforced polyimide composite material / metal bonding;

[0104] Among them, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 14%;

[0105] The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7:93:100;

[0106] The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:10.

[0107] This comparative example also provides an adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the aforementioned preparation method.

[0108] Performance Test 1

[0109] The adhesives prepared in Examples 1-4 and Comparative Examples 1-2 were respectively used for bonding the fiber-reinforced polyimide composite material to the metal, and then the lap shear strength after bonding was tested. The specific test method is as follows:

[0110] The metal sheet was washed with ethanol for 3 times at room temperature, dried at 70°C, and then polished with 400-mesh sandpaper, washed with 10% diluted hydrochloric acid and 10% diluted nitric acid for 3 times, washed with distilled water for 3 times, and dried at 70°C. Then, the adhesive prepared in Examples 1-4 and Comparative Examples 1-2 was evenly applied to the surface of the fiber-reinforced polyimide composite sheet and the metal sheet, and the adhesive coating thickness was controlled to be 100 μm. After being baked at 70°C to form a dry adhesive, the fiber was After the fiber-reinforced polyimide composite material sheet and the metal sheet are pressed together, they are pressed at a temperature of 170°C and a pressure of 2MPa for 3min, and then naturally cooled to room temperature. Then, the temperature is increased to 100°C at a heating rate of 10°C / min and kept warm for 1h; the temperature is increased to 200°C at a heating rate of 10°C / min and kept warm for 1h; the temperature is increased to 300°C at a heating rate of 10°C / min and kept warm for 1h, and naturally cooled to room temperature to obtain the test sample; the shear strength of the test sample is tested at 25°C;

[0111] The combination of fiber reinforced polyimide composite sheet and metal sheet used includes:

[0112] Combination 1: glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite sheet + aluminum metal sheet;

[0113] The second combination: glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite sheet + magnesium metal sheet;

[0114] The third combination: carbon fiber reinforced bismaleimide (carbon fiber content 30wt%) composite material plate + titanium metal plate;

[0115] The fourth combination: glass fiber reinforced bismaleimide (glass fiber content 20wt%) composite material sheet + aluminum metal sheet;

[0116] The fifth combination: carbon fiber reinforced bismaleimide (carbon fiber content 30wt%) composite sheet + magnesium metal sheet;

[0117] The test results are as follows:

[0118]

[0119] Performance Test 2

[0120] The adhesives prepared in Examples 1-4 and Comparative Examples 1-2 were respectively used for bonding the fiber-reinforced polyimide composite material to the metal, and then the lap shear strength after bonding was tested. The specific test method is as follows:

[0121] The aluminum metal sheet was washed with ethanol for 3 times at room temperature, dried at 70°C, and then polished with 400-mesh sandpaper, and then washed with 10% dilute hydrochloric acid and 10% dilute nitric acid for 3 times, washed with distilled water for 3 times, and dried at 70°C. Then, the adhesive prepared in Example 1-4 and Comparative Example 1-2 was evenly applied to the surface of the glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite material sheet and the aluminum metal sheet, and the coating thickness of the adhesive was controlled to be 100μm. Then, after being baked at 70°C to form a dry adhesive, the glass fiber reinforced polyetherimide (glass fiber content 20wt%) composite material sheet was coated with the adhesive. After the steel sheet and the aluminum sheet are pressed together, they are pressed at a temperature of 170°C and a pressure of 2MPa for 3min. After cooling naturally to room temperature, the temperature is then increased to 100°C at a heating rate of 10°C / min and kept warm for 1h; the temperature is increased to 200°C at a heating rate of 10°C / min and kept warm for 1h; the temperature is increased to 300°C at a heating rate of 10°C / min and kept warm for 1h. The test sample is obtained; the test sample is then heated to 400°C at a heating rate of 10°C / min, kept warm for 30min, cooled naturally to room temperature, and the shear strength of the test sample is tested at 25°C. The test results are as follows:

[0122]

[0123] Performance Test 3

[0124] The adhesives prepared in Examples 1-4 and Comparative Examples 1-2 were sealed and left to stand for 30 days, and then observed to see if there was a phase separation phenomenon. The results were as follows:

[0125]

[0126] It can be seen from the above results that by adding N,N'-(4,4'-methylenediphenyl)bismaleimide in the preparation of the adhesive, the shear strength and high temperature resistance of the adhesive can be improved; by adding a crosslinking agent dispersion in the preparation of the adhesive, the shear strength, high temperature resistance and uniformity of the adhesive can be improved.

[0127] Unless otherwise specified, all percentages used in the present invention are by mass.

[0128] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding, characterized in that: In a nitrogen atmosphere, N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and N,N-dimethylacetamide are mixed, stirred at room temperature for 5-10 minutes, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 4-phenylethynylphthalic anhydride and a crosslinking agent dispersion are added, and stirring is continued for 5-6 hours to obtain an adhesive for fiber-reinforced polyimide composite material / metal bonding; In the preparation of the adhesive, the sum of the mass concentrations of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 14-16%; The molar ratio of N,N'-(4,4'-methylenediphenyl)bismaleimide, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 7-8:92-93:100; The molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to 4-phenylethynylphthalic anhydride is 30:10-12; The mass ratio of N,N-dimethylacetamide to the crosslinking agent dispersion is 14-15:1; The preparation method of the crosslinking agent dispersion comprises the following steps: hydroxy silicone oil coating, zinc hydroxide coating, surface modification, and dispersion; The hydroxy silicone oil coating comprises mixing white carbon black and dimethyl hydroxy silicone oil and then ball milling to obtain hydroxy silicone oil coated white carbon black; The zinc hydroxide coating comprises mixing zinc chloride, sodium dodecylbenzene sulfonate and deionized water, stirring at room temperature for 30-40 minutes, adding hydroxy silicone oil to coat the white carbon black, continuing to stir for 40-50 minutes, centrifuging, taking a precipitate, mixing the precipitate with a sodium hydroxide aqueous solution, stirring at room temperature for 40-50 minutes, centrifuging, taking a precipitate, washing and drying the precipitate to obtain zinc hydroxide coated white carbon black; The surface modification comprises mixing N,N-dimethyl-3-aminopropyltrimethoxysilane and anhydrous ethanol, stirring at 40-45° C. for 30-40 minutes, adding zinc hydroxide to coat white carbon black, continuing to stir for 10-11 hours, centrifuging, taking a precipitate, washing, and drying the precipitate to obtain a crosslinking agent; In the dispersion, the cross-linking promoter and N,N-dimethylacetamide are uniformly mixed to obtain a cross-linking promoter dispersion.

2. The method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding according to claim 1, characterized in that: In the hydroxy silicone oil coating, the mass ratio of white carbon black to dimethyl hydroxy silicone oil is 270-275:27-30; The particle size of the white carbon black is 100 nm; The viscosity of the dimethylhydroxy silicone oil at 25° C. is 100 mPa·s.

3. The method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding according to claim 1, characterized in that: In the hydroxy silicone oil coating, the ball-to-material ratio during ball milling is 5-6:1, the rotation speed is 300-350 rpm, and the time is 35-45 min.

4. The method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding according to claim 1, characterized in that: In the zinc hydroxide coating, the mass ratio of zinc chloride, sodium dodecylbenzene sulfonate, deionized water, hydroxy silicone oil coated white carbon black, and sodium hydroxide aqueous solution is 200-250:25-26:7000-8000:570-600:3800-4000; The mass concentration of the sodium hydroxide aqueous solution is 5%.

5. The method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding according to claim 1, characterized in that: In the surface modification, the mass ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane, anhydrous ethanol, and zinc hydroxide-coated white carbon black is 18-20:7500-8000:550-600.

6. The method for preparing an adhesive for fiber-reinforced polyimide composite material / metal bonding according to claim 1, characterized in that: In the dispersion, the mass ratio of the crosslinking promoter to N,N-dimethylacetamide is 5:100-110.

7. An adhesive for fiber-reinforced polyimide composite material / metal bonding prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Adhesives for bonding polyimide resins

    CN103502328B

  • A double-sided flexible copper clad laminate and its preparation method

    CN103612464B

  • Character recognizing device

    JP1987278687A

  • High-temperature-resistant heat conduction bismaleimide adhesive low in filler content and preparation method and application thereof

    CN104531047A

  • Preparation method of polycondensation type graphene / polyimide composite adhesive

    CN106700071A